2015
DOI: 10.4315/0362-028x.jfp-14-353
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Campylobacter spp. in Retail Chicken, Turkey, Pork, and Beef Meat in Poland between 2009 and 2013

Abstract: The purpose of the present study was to determine the prevalence of thermophilic Campylobacter in poultry, pork, and beef meat at the retail level and to identify the main categories of meat representing the most significant reservoirs of Campylobacter. A monitoring study was conducted throughout Poland from 2009 to 2013. A total of 1,700 fresh meat samples were collected from supermarkets, large retail outlets, and smaller stores. Thermophilic Campylobacter species were detected in 690 (49.3%) of 1,400 poultr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
29
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 30 publications
6
29
0
1
Order By: Relevance
“…The higher prevalence of Campylobacter spp. in poultry meat compared to other meat types for human consumption has been reported in New Zealand (Wong et al., ; Mullner et al., ) and elsewhere in the world (Zhao et al., ; Hiroi et al., ; Korsak et al., ). Campylobacter upsaliensis and C. helveticus have each been isolated from 3% of beef meat samples but not detected in chicken and pork meat for human consumption with a filtration technique combining pre‐enrichment and plating using nonselective media (Lynch et al., ).…”
Section: Discussionmentioning
confidence: 94%
“…The higher prevalence of Campylobacter spp. in poultry meat compared to other meat types for human consumption has been reported in New Zealand (Wong et al., ; Mullner et al., ) and elsewhere in the world (Zhao et al., ; Hiroi et al., ; Korsak et al., ). Campylobacter upsaliensis and C. helveticus have each been isolated from 3% of beef meat samples but not detected in chicken and pork meat for human consumption with a filtration technique combining pre‐enrichment and plating using nonselective media (Lynch et al., ).…”
Section: Discussionmentioning
confidence: 94%
“…Furthermore, a recent study has reported up to 10% incidence of Campylobacter contamination of retail pork meat (Korsak et al, 2015); most likely occurring through faecal contact (Boysen and Rosenquist, 2009). Considering that many strains of Campylobacter have become multi-drug resistant (Bywater et al, 2004;Englen et al, 2005;Bernal et al, 2016;Wang et al, 2016), it is notable that reduction of pig intestinal Campylobacter load can be achieved through the simple supplementation of the diet with SUCRAM, minimising meat contamination.…”
Section: ; O'mentioning
confidence: 99%
“…Cultural and dietary differences could influence the relative contribution of sources of foodborne disease in France and the United Kingdom. For example, chicken consumption is higher in the United Kingdom (30 kg/person/year) compared to France (25 kg/person/year) (50), where other known infection sources, including ruminant offal and veal (51)(52)(53)(54), form a greater proportion of the diet. Factors associated with food preparation may also be significant, but analysis of a larger data set of French clinical isolates would be necessary to achieve a more representative description of human C. jejuni contamination routes in France.…”
Section: Fig 4 Assignment To Source Of British and French Human Clinimentioning
confidence: 99%